Local Plants as Feed Supplementation to Improve Ruminant Milk Production and Quality - Chandra Utami Wirawati; M B Sudarwanto; D W Lukman; I Wientarsih (Indonesian Center for Animal Research and Development, 2017)
Milk productivity is highly dependent on inputs used in the dairy farm. The limited source of forage or native grasses with low nutritional quality reduce production and reproduction of dairy cows. Improvement of feed quality can be conducted by various ways, including fortification and supplementation with specific substances that have the potency to increase milk production. This paper describes the potency of local plants, nutritional and bioactive substances that can be utilized to improve production and quality of milk. Some of these plants are cassava (Manihot sp), torbangun (Plectranthus amboinicus (Lour) Spreng) and katuk (Sauropus androgynus (L) Merr) leaves which are potential as feed supplement for cows, goats, and buffalo. The high protein bypass and galactogogue compounds content in these plants are factors increasing production and quality of milk.